Analisis Usahatani Padi Sawah di Kecamatan Benai Kabupaten Kuantan Singingi - Niken Kumalasari; Syaiful Hadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Development of wet land paddy farming in Benai Sub-district still faces various problems. This can be seen from the level of development of planting area and production and income received by farmers is relatively low. The purpose of this research is to know the cultivation of rice field cultivation and to analyze the income of rice field farming in Benai Sub-district of Kuantan Singingi Regency. The study used a survey method conducted from September to December 2016. A total of 80 farmers. The results showed that the land area of paddy farmers in Benai sub-district was 0.33125, the average per planted area was 1.389.38, the average of the total amount of fertilizer used was 393,073.80, the average per area of pesticide use was 330,698.80 and the average Per unit of labor usage of 14.875.52. Rice farm income average - Rp. 3,829,767.5 with the price of wet grain of Rp. 4000, the average production per cultivated area of 1,389.38 Kg and obtained R / C Ratio of 3.68. Keyword : Paddy Rice, Farming, Hospitality, Revenue